Peran PPKn Sebagai Sarana Pendidikan Hukum Dalam Meningkatkan Kesadaran Peserta Didik Mematuhi Tata Tertib Sekolah di SMA Negeri 8 Surakarta Tahun Pelajaran 2021/2022 - Dewi Gilang; Yusuf Yusuf; Sugiaryo Sugiaryo (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The purpose of this study is to determine the role of PPKn as a means of legal education in raising awareness of students complying with the school rules of SMA Negeri 8 Surakarta for the 2021/2022 academic year. This research is descriptive qualitative. The data source uses both primary and secondary. Data collection techniques through interviews, observation and documentation. In order for the data to be valid, a triangluation of sources and techniques is carried out. Analyzed using interactive qualitative techniques. Based on data analysis, it can be concluded: The role of PPKn as a means of legal education in increasing awareness of the rights and  obligations  of students is  really like getting facilities.  The role of PPKn as a means of legal education in increasing awareness of  student attendance   is really like being present on time.  The role of PPKn as a means of legal education in increasing awareness of the  neatness  of  students  is true as in full uniform.  The role of PPKn as a means of education hukum in increasing awareness of  student hygiene is indeed  true such as participating in  community service work activities.